2021
DOI: 10.1016/j.molmet.2021.101313
|View full text |Cite
|
Sign up to set email alerts
|

Extensive NEUROG3 occupancy in the human pancreatic endocrine gene regulatory network

Abstract: Objective Mice lacking the bHLH transcription factor (TF) Neurog3 do not form pancreatic islet cells, including insulin-secreting beta cells, the absence of which leads to diabetes. In humans, homozygous mutations of NEUROG3 manifest with neonatal or childhood diabetes. Despite this critical role in islet cell development, the precise function of and downstream genetic programs regulated directly by NEUROG3 remain elusive. Therefore, we mapped genome-wide NEUROG3 occupan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…2J); it has already been pointed out as a critical factor during other differentiation processes such as in thymocyte development 35 . Also, previous studies from our group reported it to be a direct target of Neurog3 36 .…”
Section: Delineating Transcriptional Regulators During Mouse Islet Ce...mentioning
confidence: 59%
See 2 more Smart Citations
“…2J); it has already been pointed out as a critical factor during other differentiation processes such as in thymocyte development 35 . Also, previous studies from our group reported it to be a direct target of Neurog3 36 .…”
Section: Delineating Transcriptional Regulators During Mouse Islet Ce...mentioning
confidence: 59%
“…4D), indicating that in the human in-vitro context, there is a similar switch from MAFB to MAFA, in developing towards fully functional β-cells, to the one reported in rodents 61 . GLIS3, which we previously found as a direct target of NEUROG3 in pancreatic endocrine progenitor cells 36 , was classified as SC-EC (Fig. 4E).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…A previous study proposed that Neurog3 can start endocrine development by regulating a set of TFs that are related to the proliferation and maturation of endocrine cells (Napolitano et al 2015). Islet cells cannot be formed in mice lacing Neurog3, leading to diabetes (Schreiber, et al, 2021).…”
Section: Scmte Finds Crucial Tf For Pancreatic Developmentmentioning
confidence: 99%
“…Pax4 is an important regulator for β cells construction. Experiments show that mice lacking Pax4 die after a few days because they lack mature β cells (Napolitano, et al, 2015;Schreiber, et al, 2021). Insm1 maintains mature β-cell functions (Jia, et al, 2015).…”
Section: Scmte Finds Crucial Tf For Pancreatic Developmentmentioning
confidence: 99%